Soil Vegetation Engineering Model to Maintain Distribution from Water Debit at Watershed Area of Krueng Pase North Aceh - Halim Akbar (Recent Progress in Plant and Soil Research Vol. 3, 2021)
The increasing land use changes can alter the existence of vegetation cover on open land such as paddy fields and mooring into grass or shrubs, plantations, and tend to increase the proportion of land area built. Vegetative technology is often chosen because in addition to reduce erosion and sedimentation in rivers also have economic value (productive crops) and can restore the water system of a watershed. The researcherr used a model of soil vegetation engineering to maintain water distribution in Krueng Pase watershed in North Aceh District. To achieve these objectives, a model of grass vegetation was adopted as a water and land conservation strategy in the Krueng Pase Basin of North Aceh Regency. The model of grass vegetation can withstand runoff and increase infiltration. The average of plant retention to hold rain water in this research is for land (without vegetation) 33%, grass and herbs 77%, and shrub 81%. Meanwhile, to know the water denit used non-linear regression equation. The results show that vegetation grasses and other soil cover crops can withstand erosion and sediment. The relationship between water discharge and sediment was obtained by coefficient of determination (R2 = 0.98). This shows the water debit due to precipitation affecting the sedimentation volume.